Characterization of single nucleotide polymorphism in the 5'-untranslated region (5'-UTR) of Lactoferrin gene and its association with reproductive parameters and uterine infection in dairy cattle - Abolfazl Hajibemani; Hassan Sharifiyazdi; Abdolah Mirzaei; Abbas Rowshan Ghasrodashti (Veterinary Research Forum, 2012)
Uterine infection is one of the reproductive diseases that can have disturbing postpartumuterine health in cattle. Therefore, identification of resistant genotypes to uterine infection isimportant. Lactoferrin (LF) is one of the major antimicrobial compounds in the normal uterinedischarges of cows. We hypothesized that allelic diversity in LF gene may contribute tosusceptibility or resistance to uterine infection. We investigated the single nucleotidepolymorphism genes identified in the 5' untranslated region (5'-UTR, position +32) of the LF geneusing Allele-specific PCR method in cows with and without uterine infection. Blood samples werecollected from 89 multiparous Holstein dairy cows with a history of uterine infection (n = 51), andcows without disease as the control group (n= 38). The results indicated the presence of differentproportion of polymorphisms (G > C) in the 5'-UTR area of cows in the all groups. The results ofAllele specific PCR was in complete agreement with sequencing method. Statistical analysis did notshow any statistically significant correlation between disease and SNP in 5'-UTR. While, there was asignificant difference in the mean of reproductive parameters of cows without polymorphismcompare to those of with SNP in 5'-UTR. Cows with +32:CC genotype and +32:GC genotype (cowswith SNP in UTR) had lower average of services per conception and days open compared to cowswith the +32:GG genotypes. However, no significant difference in the calving to first service wasfound between these genotypes. Further studies will be required to determine critical SNPs in LFgene and status of the risk of uterine infection and embryo survival in cows.